Review of gender-responsive sex education material and methods in the context of islamic education - Luluk Ifadah; Yuni Setya Hartati; Dea Puji Saputri; Puput Sukma Ayu Wulandari; Mohamad Ardin Suwandi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The discussion of material and methods for gender-responsive sex education is an important issue within the context of Islamic education, approached with sensitivity to gender differences. This study aims to explore how sex education can be aligned with Islamic teachings that emphasize moral values, ethics, and gender justice. The study finds that the material for sex education in Islamic education must encompass aspects of reproductive health, ethics of inter-gender relationships, and the value of purity in Islamic teachings. Additionally, the teaching methods applied should be sensitive to gender issues, avoiding stereotypes, and providing equal space for both men and women in understanding sexuality. This research also identifies various challenges, such as conservative perceptions in society and the unpreparedness of parents as educators in delivering sex education materials. It can be concluded that, with the appropriate materials and methods, gender-responsive sex education in Islamic education will contribute to the development of individuals who are healthy physically, mentally, and spiritually, while respecting the values of gender equality and justice.